1996
DOI: 10.1159/000285015
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Factors in the Development of Mood Disorders with a Seasonal Pattern

Abstract: The psychiatric records of a 7-year period were searched for cases with seasonal mood disorders. Among 358 cases with a mood disorder there were 41 patients with 3 or more admissions, 4 of which were demonstrating a seasonal pattern. It was found that the depressive or manic episodes of these patients were anniversary reactions associated with intense traumatic experiences in childhood, adolescence or adulthood. The seasonal pattern of the depressive episodes fulfilled the DSM-IV diagnostic criteria. The time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
5
0
2
Order By: Relevance
“…Treatment of these patients to prevent readmission is difficult (Hawton et al, 1998;Bennewith et al, 2002), with no definite strategies of proven benefit, although a recent study suggested that patients who received a psychosocial assessment were half as likely to poison themselves again (Kapur et al, 2002). Many factors determining such behaviour have been proposed, some of these, such as events or anniversaries, are specific to each patient (Beratis et al, 1996), but other factors relate to external influences and include times of the year (Beratis et al, 1996;Suhail & Cochrane, 1998) and days of the week (Hulse et al, 2001). Predicting admission patterns may be used to focus medical care and improve management and perhaps even prevent self-poisonings.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of these patients to prevent readmission is difficult (Hawton et al, 1998;Bennewith et al, 2002), with no definite strategies of proven benefit, although a recent study suggested that patients who received a psychosocial assessment were half as likely to poison themselves again (Kapur et al, 2002). Many factors determining such behaviour have been proposed, some of these, such as events or anniversaries, are specific to each patient (Beratis et al, 1996), but other factors relate to external influences and include times of the year (Beratis et al, 1996;Suhail & Cochrane, 1998) and days of the week (Hulse et al, 2001). Predicting admission patterns may be used to focus medical care and improve management and perhaps even prevent self-poisonings.…”
Section: Discussionmentioning
confidence: 99%
“…They might unconsciously replace the real but traumatic psychosocial cause of their depression by more neutral and distant but less traumatic physical causes, such as winter darkness. In particular, Beratis et al (1996) found that depressive episodes can be anniversary reactions associated with intense traumatic experiences in childhood, adolescence or adulthood. The time and sometimes the place of the traumatic event acted as the trigger eliciting the clinical symptoms.…”
Section: Explanation Of Antidepressant Effectsmentioning
confidence: 99%
“…Psychiatry recognizes anniversaries as another type of recurrent event that can give rise to annual depressions with purely psychosocial causes. Indeed, some apparent cases of SAD have been determined, on re‐examination, to be more accurately diagnosed as ‘anniversary reactions’ connected with bereavements or other traumatic incidents in patients’ lives (Beratis, Gourzis & Gabriel 1994; 1996). The patients described in these particular studies experienced annually recurring depressions initially diagnosed as SAD, but on closer investigation it was found that the memories and associations of an event, not the climate, were precipitating the depressive episodes at the same time each year.…”
Section: Avatip: Heat‐haze and Nostalgiamentioning
confidence: 99%